2008
DOI: 10.1186/cc6789
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different pain scoring systems in critically ill patients in a general ICU

Abstract: Background Pain in critically ill patients in the intensive care unit (ICU) is common. However, pain assessment in critically ill patients often is complicated because these patients are unable to communicate effectively. Therefore, we designed a study (a) to determine the inter-rater reliability of the Numerical Rating Scale (NRS) and the Behavioral Pain Scale (BPS), (b) to compare pain scores of different observers and the patient, and (c) to compare NRS, BPS, and the Visual Analog Scale (VAS) for measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
133
1
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 27 publications
4
133
1
10
Order By: Relevance
“…The VAS may be considered a continuous measurement scale (van Dijk et al 2012). Accurate administration requires: a clearly readable scale with descriptors, the participant's understanding and co-operation, and adequate response time (van Dijk et al 2012, Ahlers et al 2008). The VAS is suitable for obtaining self-reports on the status of pain from ventilator-dependent patients for both routine clinical and research purposes (Ahlers et al 2008, Aissaoui et al 2005, HamillRuth & Marohn 1999.…”
Section: Methodsmentioning
confidence: 99%
“…The VAS may be considered a continuous measurement scale (van Dijk et al 2012). Accurate administration requires: a clearly readable scale with descriptors, the participant's understanding and co-operation, and adequate response time (van Dijk et al 2012, Ahlers et al 2008). The VAS is suitable for obtaining self-reports on the status of pain from ventilator-dependent patients for both routine clinical and research purposes (Ahlers et al 2008, Aissaoui et al 2005, HamillRuth & Marohn 1999.…”
Section: Methodsmentioning
confidence: 99%
“…The BPS was completed for all patients receiving mechanical ventilation; the NRS was either estimated by the bedside nurse or obtained from the patient if the patient was able to respond. Having a bedside nurse estimate the NRS score is a questionable practice, because this study 31 indicated that the NRS score as reported by the patient correlated with the score estimated by the Although designed for noncommunicative critically ill patients, the NPAT has not been validated in this population of patients.…”
Section: Behavioral Pain Scalementioning
confidence: 96%
“…Ahlers et al 31 obtained 371 independent determinations of the BPS and NRS (when possible) in 113 critically ill patients. The BPS was completed for all patients receiving mechanical ventilation; the NRS was either estimated by the bedside nurse or obtained from the patient if the patient was able to respond.…”
Section: Behavioral Pain Scalementioning
confidence: 99%
“…(1)(2)(3)(4)(5) Moderate to severe pain is a common phenomenon experienced by patients in the Intensive Care Units (ICUs). (5) Multiple intrinsic and extrinsic sources contributing to this pain include underlying health conditions or disease, trauma, and routine care procedures.…”
Section: Introductionmentioning
confidence: 99%